The Processing of Nitrocellulose from Rhizophora, Palm Oil Bunches (EFB) and kenaf fibres as a Propellant Grade - Yolhamid, Mohd Najib Abdul Ghani; Ibrahim, Farizha; Amir, Mohamad Abu Ubaidah; Ibrahim, Rushdan; Adnan, Sharmiza; Yahya, Muhd Zu Azhan (International Journal of Engineering and Technology, 2018)
Nitrocellulose based powders are extensively in military application used as propellant in bullets, shells, and various missiles for tube munitions. In this study, Rhizophora, Palm Oil Bunches- Empty Fruit Bunches (EFB) and kenaf fibres were used as raw materials to produce nitrocellulose suitable for replace gunpowder. All raw materials are converted to dissolving pulps before nitrocellulose are synthesized. The characteristics of both dissolving pulps and nitrocellulose are determined. The result shows that the nitrocellulose fromÂ  Rhizophora, Palm Oil Bunches- Empty Fruit Bunches (EFB) and kenafÂ  have a tendency as propellant.